The concept of tourism cluster as a path to rural success: Slovakia, Liptov region - SZÉKELY, Vladimír (Discussion Papers, 2011)
Changes in the political and economic management in the former socialist countries have greatly influenced the differentiation of official conceptions concerning their spatial development. These facts also influence the spatial choice behaviour of population and the consequent creation of new spatial structures. Rural population in the 20th century had to face the challenge of developing industrialisation, which have also directly impacted agricultural production and forestry. The industrialisation process was the cause of increased urbanising processes in Slovakia in the later half of the 20th century. The selective exodus of (predominantly) young people from rural areas caused their depopulation with the parallel reduction of their developmental potential. Rural areas acquire the more-or-less generally accepted status of problematic areas. The political and economic changes in Czechoslovakia (and also in other former socialist countries), which triggered the transformation of the whole society at the beginning of the 1990s, represented an incentive for a more distinct spatial differentiation of the rural areas. Rural municipalities and rural areas compete with each other on regional, national or European levels. Every (?) rural spatial unit tries to occupy the place among winners in competition for people and capital. The aim of the article is to present a basic idea of the term “successful rural area” which is a kind of final picture of the influence of selected endogenous and exogenous factors on its socio-economic development. One of the possible alternative paths to (economic) success in rural area will be demonstrated by showing the example of how the concept of tourist cluster has been applied in the region of Liptov endeavouring for a more efficient use of (not only) the natural potential existing in its territory.